EEC: its integration role in region, examples of law problems in financial-tariff aspect and meaning for Kazakhstan’s economy in their context for today - Nurbekova, G.T.; Polevoy, S.V. (KSU Publ., 2018)
Connection of Eurasian Economic Union is the newest integration project at large of Commonwealth of Independent States. Its foundation was determined by the fact, that previous integration alliances like CU and CIS were feeble in their economic function. The biggest part of experts estimate new format of EEU positively, because they think that it is going to be better than ex in aspect of economic cooperation. These statements are not unreasonable. However, on the assumption of political and law tendencies in this state block, EEU’s legislation also has a set of unfounded preferences, which induce discussions about its foundation and following collisions. Many points of financial – tariff regulation are written in very indistinct manner, and also their law content is written in favour of other participants of integration agreement, or just it doesn’t match with economic and political interests of Republic of Kazakhstan. Similar facts shouldn’t be out of consideration, because Kazakhstan became a participant of all customs agreements in integration projects on the CIS territories voluntarily, and it has all rights to rely on profits from its membership in EEC. In consequence of these integration processes, problems, appearing on practice, must be marked for the next decision and such need was a task for this article
ЕАЭО: аймақтағы оның интеграциялық рөлі, қаржылық жəне тарифтік аспектілердегі құқықтық мəселелердің мысалдары жəне бүгінгі күні олардың контекстіндегі Қазақстан экономикасы үшін маңызы
ЕАЭС: его интеграционная роль в регионе, примеры правовых проблем в финансово-тарифном аспекте и значимость для экономики Казахстана в их контексте на сегодняшний день
Keywords: integration; EEU; economical – law problems; Republic of Kazakhstan; export; customs law; business competition; financial – tariff; regulation; political interests; integration block; union; law regulation; .